The Khotanese Sudhanavadana - De Chiara, Matteo (Beiträge zur Indologie, 2013)
The Sudhanavadana is an agreeable tale which relates a story of a previous life of the Buddha: that of prince Sudhana and his wife, the fairy princess Manohara. Core of the work is the journey of Sudhana in search of his lost consort. Written in a Middle Iranian Language, i.e. Khotanese, spoken in Central Asia and used to compile Buddhist works, this tenth-century Late Khotanese poem is preserved in three virtually complete manuscripts and seven fragments all found in Dunhuang. The manuscripts and fragments must go ultimately back to a single source, but what remains are two distinct recension.